2015
DOI: 10.1002/gcc.22263
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and follow‐up of five CML patients with new BCR–ABL1 fusion transcripts

Abstract: We report five chronic myeloid leukaemia (CML) patients in whom we identified and characterized undescribed BCR-ABL1 fusion transcripts. We investigated the precise features of the molecular rearrangements and the minimal residual disease follow-up for these five patients. Three resulted from new rearrangements between the BCR and ABL1 sequences (the breakpoints being located within BCR exon 13 in two cases and within BCR exon 18 in one case). The other two cases revealed a complex e8-[ins]-a2 fusion transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
(65 reference statements)
1
6
0
Order By: Relevance
“…To guarantee that ABL1 protein‐coding sequence is kept in‐frame, breakpoint may occur within the BCR exon, and a sequence insertion may take place. In such cases, the breakpoint within the BCR exon and the inserted sequence are usually unique, as reported in previous studies (Sorel et al , ; Huet et al , ). In the current study, in addition to transcripts e19a2, e13a3/e14a3 and e1a2, 15 different fusion transcripts were identified in 19 patients.…”
Section: Discussionsupporting
confidence: 55%
“…To guarantee that ABL1 protein‐coding sequence is kept in‐frame, breakpoint may occur within the BCR exon, and a sequence insertion may take place. In such cases, the breakpoint within the BCR exon and the inserted sequence are usually unique, as reported in previous studies (Sorel et al , ; Huet et al , ). In the current study, in addition to transcripts e19a2, e13a3/e14a3 and e1a2, 15 different fusion transcripts were identified in 19 patients.…”
Section: Discussionsupporting
confidence: 55%
“…Other studies on different ethnic groups identified atypical BCR-ABL1 transcripts on different parts of BCR and ABL1 exons such as e1a3, e2a1, e6a2, e8a2, e13a3 (or b2a3) and e14a3 (or b3a3) [13][14][15]. Other transcripts can be identified such as e12a3, e6a3, e19a3, e20a2 and e20a3 [7].…”
Section: Discussionmentioning
confidence: 97%
“…Although little is known about the function of PRDM12 in oncogenesis, previous studies showed that PRDM12 might act as a tumor suppressor gene in human chronic myeloid leukemia (CML) [ 66 , 67 , 68 ]. In approximately 15% of CML patients, deletions occur on the derivative chromosome 9 [der(9)] within a region containing the PRDM12 gene.…”
Section: Exploring Novel Prdm12 Functions: Cancermentioning
confidence: 99%